2017
DOI: 10.1002/stc.2051
|View full text |Cite
|
Sign up to set email alerts
|

Demand-based optimal design of oscillator with parallel-layout viscous inerter damper

Abstract: SummaryIn this study, a demand-based optimal design method is proposed for an oscillator (a single-degree-of-freedom system) with a parallel-layout viscous inerter damper (PVID). The proposed design method overcomes some deficiencies of the existing method, which is based on the fixed-point theory and is mainly suitable for tuned mass dampers. Moreover, for the fixed-point method, the inherent damping of the primary structure is neglected, and the global optimal solution cannot be obtained.The proposed method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 26 publications
2
62
0
Order By: Relevance
“…Therefore, the selection of a rational parameter set for the design of SPIS‐II based on only the displacement response is difficult. The control cost, which can be represented by the force response of the inerter system, should be considered in the case of SPIS‐II, as determined in a previous study . Hence, the variation patterns of the force response for SPIS‐II (in the form of the dimensionless root‐mean‐square response σFitalicIS2/πω0S0) were also obtained in the present study, as shown in Figure , in which.…”
Section: Theoretical Analysis Of Basic Types Of Inerter Systemsmentioning
confidence: 70%
See 1 more Smart Citation
“…Therefore, the selection of a rational parameter set for the design of SPIS‐II based on only the displacement response is difficult. The control cost, which can be represented by the force response of the inerter system, should be considered in the case of SPIS‐II, as determined in a previous study . Hence, the variation patterns of the force response for SPIS‐II (in the form of the dimensionless root‐mean‐square response σFitalicIS2/πω0S0) were also obtained in the present study, as shown in Figure , in which.…”
Section: Theoretical Analysis Of Basic Types Of Inerter Systemsmentioning
confidence: 70%
“…(b) A comparison of the M1 and M3 results reveals that M1 produces higher displacement and force responses for a given inerter‐mass ratio μ . (c) A comparison of the M1 and M4 results indicates that the demand‐based numerical optimization method is equivalent to the presently proposed response mitigation method.…”
Section: Design Examplementioning
confidence: 99%
“…According to the actual production capacity and device design requirements, the fluctuation in the sloshing height of the liquid in the storage tank will reach the minimum value at a high control cost within the range of the three variable parameters ( , , and ). In the actual optimization design of the VIS, certain control requirements are necessary to lower the control costs [25]. As mentioned above, and are selected as the objective indicators.…”
Section: Optimization Of the Hybrid Methods Designmentioning
confidence: 99%
“…The disadvantage of the fixed method is that it neglects the inherent damping of the primary structure, and a limitation is introduced because an empirically equivalent mass ratio is used. Pan et al [25] developed a demand-based optimal design for a single-degree-of-freedom structure considering the inherent damping ratio of the primary structure.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For passive structural response control, hysteretic dampers-generally made of metals with excellent ductility such as mild steel-are widely used as energy dissipation devices (EDDs) to control structural seismic response. 1,2 For passive structural response control, hysteretic dampers-generally made of metals with excellent ductility such as mild steel-are widely used as energy dissipation devices (EDDs) to control structural seismic response.…”
Section: Introductionmentioning
confidence: 99%